1984
DOI: 10.3758/bf03202398
|View full text |Cite
|
Sign up to set email alerts
|

Minicomputer-administered tasks in the study of effects of sustained work on human performance

Abstract: Six tasks administered on a MINC·ll minicomputer were used in studying the effects of long, continuous work periods and fatigue on physical and cognitive task performance. Submaximal physiological workload measurement was done during one of these tasks for a subject walking on a treadmill. The MINC·II system is described, as are the six tasks programs. Four of these tasks measured various types of reaction times, another involved complex information processing, and one appraised moods, physical symptoms, fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Between performance bouts, the subjects were free to engage in a variety of activities, including reading, conversation, board games, studying, darts, and cards. Monitors stayed with them at all times between test bouts to ensure that they remained awake, and a senior investigator administered the performance tests without the aid of a computer (see Ryman, Naitoh, & Englund, 1984, for a description of a new computerbased system for task administration).…”
Section: Methodsmentioning
confidence: 99%
“…Between performance bouts, the subjects were free to engage in a variety of activities, including reading, conversation, board games, studying, darts, and cards. Monitors stayed with them at all times between test bouts to ensure that they remained awake, and a senior investigator administered the performance tests without the aid of a computer (see Ryman, Naitoh, & Englund, 1984, for a description of a new computerbased system for task administration).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, unique uses of computers, wherein subjects become subject-experimenters have been reported in sustained work studies (Mullaney, Kripke, Fleck, & Okudaira, 1983;Ryman, Naitoh, & Englund, 1984). New methodologies (Englund, 1981;Naitoh, Englund, Moses, & Spinweber, 1979), novel methods of data transformation (Thome, Genser, Sing, & Hegge, 1983), and different variables (Englund et al, 1983;Thome et al, 1983) have been identified.…”
Section: Carl E Englundmentioning
confidence: 99%
“…The results on these measurements have been presented elsewhere Naitoh, Englund, & Ryman, 1982). A description of the computerized portion of the NHRC Performance Assessment Battery (PAB) utilized in the sustained operations (SUSOPS) series of studies at the lab was provided in Ryman, Naitoh, and Englund (1984) (see also Naitoh, 1981, and Naitoh et al, 1982. The other independent variables were sustained work and sleep loss.…”
Section: Measurementsmentioning
confidence: 99%